Multilevel selection on offspring size and the maintenance of variation - Cameron, Hayley; Johnson, Darren; Monro, Keyne; Marshall, Dustin (Dryad, 2020)
Multilevel selection on offspring size occurs when offspring fitness
depends on both absolute size (hard selection), and size relative to
neighbours (soft selection). We examined multilevel selection on egg size
at two biological scales: within clutches and among females, for an
external fertilising tubeworm. We exposed clutches of eggs to two sperm
environments (limiting and saturating) and measured their fertilisation
success. We then modelled environmental (sperm) differences in hard and
soft selection on individual eggs, as well as selection on clutch-level
traits (means and variances). Hard and soft selection differed in strength
and form depending on sperm availability – hard selection was consistently
stabilising; soft selection was directional and favoured eggs relatively
larger (sperm limitation) or smaller (sperm saturation) than the
clutch-mean. At the clutch-level, selection on mean-egg size was largely
stabilising; whilst selection on within-clutch variance was weak, but
generally negative – although some correlational selection occurred
between these two traits. Importantly, we found that the optimal
clutch-mean egg size differed for mothers and offspring, suggesting some
antagonism between the levels of selection. We thus identify several
pathways that may maintain offspring-size variation: environmentally
(sperm)-dependent soft selection; antagonistic multilevel selection; and
correlational selection on clutch-means and variances. Multilevel
approaches are powerful, but seldom used, tools for studies of offspring
size and we encourage their future use.
Data used to model multilevel selection on egg size under sperm saturating
(H) and sperm limiting (L) conditions for the broadcast spawning
polycheate, Galeolaria caespitosa. We used a split-clutch design to
conduct in vitro fertilisations, whereby each female's clutch was
split across 2 replicate fertilisations (Rep) per sperm
treatment. We then measured the size-specific fertilisation success of all
eggs within these clutch subsamples as a binary response variable
(0 = unsuccessful eggs; 1 = successfully fertilised eggs). Note that
values of clutch-mean in the dataset represents the mean-egg size of each
female's clutch measured from photographs taken prior to
fertilisation. Egg size represents the inital size of each indiviual
egg prior to fertilisation, and has been back-calculated from
measurements taken after fertilisation using equations that describe these
relationships.